Right-sided aortic arch with the retroesophageal left subclavian artery as the fourth branch - Chai, Ok Hee; Han, Eui-Hyeog; Kim, Hyoung Tae; Song, Chang Ho (Anatomy & cell biology, 2013)
We present a rare variation of the right-sided aortic arch with the retroesophageal left subclavian artery as the forth branch found in a cadaver of an 89-year-old Korean woman during a routine dissection. In this case, the first branch that arose from the ascending aorta was the left common carotid artery, which crossed ventral to the trachea in a left cephalic direction, followed by the right common carotid artery and then the right subclavian artery. Distal to these branches the aortic arch ran dorsally, passing between the esophagus and the vertebra. The left subclavian artery arose from the descending portion of the aortic arch, crossing over to the left upper extremity behind the esophagus. This anomaly was not accompanied by congenital heart disease. Accurate information regarding this variation is of great importance to surgeons for its early identification and preservation during interventions and to radiologists for precise interpretation of angiograms.